Noise minimization limits in multichannel integrated circuits dedicated to neurobiology experiments. (May 2016) - Kmon, P.
Abstract: The paper presents an analysis of problems associated with the area and power reduction of readout circuits used in multichannel neurobiology experiments, in relation to noise minimization. The noise limits of a single channel considered as a function of the silicon occupation and power consumption are analyzed for an amplifier working with capacitive feedback. The paper also presents an efficient method of noise minimization in multichannel recording systems used in neurobiology experiments, when the power budget and silicon area per single recording channel are strictly limited. The proposed idea was verified in an eight-channel prototype integrated circuit fabricated in CMOS 180 nm process. The prototype IC measurements show that with the use of the proposed method, one can decrease the recording channels' noise two times with the existing dedicated power and area budget.